Kebijakan Pengelolaan Pertahanan dan Dampak Kebijakannya di Perbatasan Indonesia Malaysia - Muhammad Haris Zulkarnain; Kholis Roisah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2018)
Indonesia is the largest archipelagic country that has several border areas, one of which is Malaysia. The border region has a strategic role as the main gateway of a country and representation of political, economic, socio-cultural, defense and security aspects. Social and economic problems that are often faced in the border areas of Indonesia-Malaysia. The research aims to analyze defense management policies and the impact of its policies in the Indonesia-Malaysia border region. The research method used is normative juridical and the data used is secondary data with qualitative analysis. The results of this study that: First, the last decade since the reform era, the state is seriously trying to strengthen defense as one of the important elements to safeguard the sovereignty of the Unitary State of the Republic of Indonesia. The efforts are made through various methods such as formal, institutional and practical legal. The approach used in the country's defense and security concept in the border region is through Sishankamrata. Second, Second, the defense policies to safeguard national sovereignty at the border in its implementation have a number of obstacles, as limited infrastructure, length of state borders, limited security personnel, and overlapping authority between institutions and ministries in managing border areas. Indonesia merupakan negara kepulauan terbesar yang memiliki beberapa daerah perbatasan, salah satunya dengan Malaysia. Wilayah perbatasan memiliki peran strategis sebagai pintu gerbang utama dari suatu negara dan representasi dari aspek politik, ekonomi, sosial budaya, pertahanan dan keamanan. Permasalahan sosial dan ekonomi yang sering dihadapi di daerah perbatasan Indonesia dan Malaysia. Penelitian bertujuan untuk menganalisis kebijakan pengelolaan pertahanan dan dampak kebijakannya di wilayah perbatasan Indonesia-Malaysia. Metode penelitian yang digunakan adalah yuridis normatif dan data yang digunakan adalah data sekunder dengan analisa kualitatif. Hasil penelitian ini bahwa: Pertama, dekade terakhir sejak era reformasi, negara serius berupaya memperkuat pertahanan sebagai salah satu elemen penting untuk menjaga kedaulatan Negara Kesatuan Republik Indonesia. Upaya yang dilakukan melalui beragam cara seperti legal formal, institusional, dan praktis. Pendekatan yang digunakan dalam konsep pertahanan keamanan negara di wilayah perbatasan adalah melalui Sishankamrata. Kedua, kebijakan pertahanan untuk menjaga kedaulatan negara di perbatasan dalam implementasinya tidak lepas dari sejumlah kendala yang dihadapi, yaitu keterbatasan sarana prasarana, panjangnya batas wilayah negara, keterbatasan personil aparat keamanan, dan tumpang tindih kewenangan antar lembaga dan kementerian dalam mengelola wilayah perbatasan.